Role of Ducting in Relativistic Electron Loss by Whistler‐Mode Wave Scattering. Issue 11 (12th November 2021) - Artemyev, A. V.; Demekhov, A. G.; Zhang, X.‐J.; Angelopoulos, V.; Mourenas, D.; Fedorenko, Yu V.; Maninnen, J.; Tsai, E.; Wilkins, C.; Kasahara, S.; Miyoshi, Y.; Matsuoka, A.; et al.
Abstract: Resonant interactions of energetic electrons with electromagnetic whistler‐mode waves ( whistlers ) contribute significantly to the dynamics of electron fluxes in Earth's outer radiation belt. At low geomagnetic latitudes, these waves are very effective in pitch angle scattering and precipitation into the ionosphere of low equatorial pitch angle, tens of keV electrons and acceleration of high equatorial pitch angle electrons to relativistic energies. Relativistic (hundreds of keV), electrons may also be precipitated by resonant interaction with whistlers, but this requires waves propagating quasi‐parallel without significant intensity decrease to high latitudes where they can resonate with higher energy low equatorial pitch angle electrons than at the equator. Wave propagation away from the equatorial source region in a non‐uniform magnetic field leads to ray divergence from the originally field‐aligned direction and efficient wave damping by Landau resonance with suprathermal electrons, reducing the wave ability to scatter electrons at high latitudes. However, wave propagation can become ducted along field‐aligned density peaks (ducts), preventing ray divergence and wave damping. Such ducting may therefore result in significant relativistic electron precipitation. We present evidence that ducted whistlers efficiently precipitate relativistic electrons. We employ simultaneous near‐equatorial and ground‐based measurements of whistlers and low‐altitude electron precipitation measurements by ELFIN CubeSat. We show that ducted waves (appearing on the ground) efficiently scatter relativistic electrons into the loss cone, contrary to non‐ducted waves (absent on the ground) precipitating only < 150 keV electrons. Our results indicate that ducted whistlers may be quite significant for relativistic electron losses; they should be further studied statistically and possibly incorporated in radiation belt models. Key Points: Near‐equatorial and ground‐based measurements of whistler‐mode waves are accompanied by relativistic electron precipitation In the presence (absence) of ducted wave propagation, as monitored by propagation to the ground, the precipitating electron energies are above (below) 150 keV Ducted whistler‐mode waves may play a key role in relativistic electron loss in the inner magnetosphere